Modelling of power curve equation for small-scale vertical axis hydrokinetic turbine - Wan Ismail, Ibrahim; Mohd Rusllim, Mohamed; Raja Mohd Taufika, Raja Ismail (Springer Science and Business Media Deutschland GmbH, 2022)
In this paper, the power curve equation model using a vertical axis turbine for small-scale hydrokinetic energy harnessing real-time simulation is proposed. The modelling technique is based on an analytical approximation method on the CP-TSR curve characteristic of the H-Darrieus turbine. In this work, the CP-TSR curve characteristic is generated and derived through a simulation process using QBlade and MATLAB software. The Root Mean Square Error (RMSE) method is implemented to obtain the most accurate polynomial approximation equation to represent the H-Darrieus turbine. The 6th polynomial equation has been chosen as a turbine power equation model due to the least RMSE value. The results indicated that the proposed power equation model enhanced the energy conversion with 86.92% efficiency compared to the other model.